The design and investigation of two storage/retrieval mechanisms of the cylindrical automated storage and retrieval system - Janilionis, Vytautas; Bazaras, Žilvinas (Transport, 2013)
The objective of this research is to propose and investigate a new design of the Cylindrical Automated Storage and Retrieval System (C-AS/RS) and provide a performance comparison of the two types of Storage/Retrieval Mechanisms (SRM I and SRM II) for the system configurations with different input/output location numbers and positions. Although the better performance is expected from of the system with SRM II, because it contains the vertically independent moving load handling devices (LHDs) compared to the interconnected LHDs used in SRM I, the vertically independent movement requires more sophisticated equipment which should be considered by the system designers. Hence, the performance investigation is required to identify the differences between the two types of the SRMs for different C-AS/RS configurations. For this purpose, the detailed simulation model of the C-AS/RS was developed, investigated for various combinations of system parameters and the multiple regression models for predicting system performance measures were developed (adjusted R-square greater than 0.83 for all models). The differences of the performance measures were evaluated and showed that SRM II achieved 7÷20% higher load retrieval rates compared to SRM I for all investigated parameter combinations. The investigation also showed that the number and position of the input/output locations had a significant impact on the system performance.First Published Online: 24 Dec 2013